Comparative analysis of effectiveness of some students’ physical culture training methodic - A.Yu. Osipov; M.D. Kudryavtsev; S.S. Iermakov; M.G. Yanova; T.V. Lepilina; I.I. Plotnikova; O.S. Dorzhieva (Physical Education of Students, 2017)
Introduction: scientific researches witness about presence of serious tendency to weakening students’ everyday motor activity and absence of motivation to physical culture and sports practicing. Some specialists offer to solve this problem by making physical culture classes more oriented on sports. At the same time there are studies, offering to use methodic of cardio-power training. Purpose: comparative analysis of effectiveness of different programs on Physical culture trainings with the help of sport oriented approach and functional-power training. The main criterion of trainings’ effectiveness was the level of physical and functional fitness of students’ organism to physical loads. Material: in the research students (n=600: boys - n=300, girls - n=300, age - 19-20 years) participated. Selection of students was fulfilled, considering indicators of body mass. We used the methods of physical condition control and assessment (control tests) and functional fitness (functional tests). Besides, we considered indicators of busy mass by students’ regular weighing. Results: we found some increase of body mass of students, who attended different sport specialization trainings. Boys and girls (athletic gymnastic and ping pong) demonstrated confident body mass increase in average by 3-4 kg during academic year Students, practicing cardio-power training - HOT IRON- practically did not increase body mass. Difference in body mass indicators of such students between beginning of trainings and at the end of the researches was insignificant (±0.3 kg). Tests’ results witness about general reduction of indicators of students’ main physical qualities during academic year. Significant increase of physical strength was found only in students, specializing in athletic gymnastic (boys and girls). Students of cardio-power training - HOT IRON-demonstrated confident increase of indicators of physical strength, general endurance and flexibility. Conclusions: our results witness that there is a demand in corrections of students’ physical culture training methodic. Their base is programs of sport oriented physical education. With it, it is necessary to compulsory consider dynamic of body mass changes and targeted application of cardio-power training programs.